Multidimensional Coefficient Approach to Comfort Evaluating for High-speed Train - Wang Hai Yong; Wang Xiao Ming; Dang Jian-wu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the complex operation environment of high-speed trains, the comprehensive evaluation index systems with high scientificity and measurability have been established after the all-round analysis of various effects on comfort for high-speed train. Meanwhile, a comprehensive evaluation method on comfort for high-speed train has been built by the rough set theory and multidimensional coefficient theory. The real examples have shown that the evaluating process is scientific, intuitive and convenient. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4363